Bi'ah Lughawiyyah in Arabic Language Learning: A Case Study of a Multicultural School in Jakarta - Hafifah Fitriana; Abdul Hafidz bin Zaid (Universitas Islam Negeri Maulana Malik Ibrahim Malang, 2026)
This study aims to describe the implementation of bi'ah lughawiyyah in Arabic language learning at the Sudan Asia Afrika School in Jakarta and to examine the influence of the language environment on students’ Arabic language skills. The research addresses the following question: how does the implementation of bi'ah lughawiyyah contribute to students’ Arabic language acquisition in a multicultural school environment? This study was motivated by the importance of the language environment in supporting the success of Arabic language learning, especially in schools with diverse cultural backgrounds. The study employed a qualitative method with a case study approach. Data were collected through observation, interviews, and documentation involving madrasah leaders, teachers, and students as research informants (n=1 school leaders, 4 teachers, and 10 students). The results showed that the school actively implements the use of Arabic in both learning activities and daily communication. Fusha Arabic is used in classroom instruction according to the Sudanese curriculum, while amiyah is used in informal interactions between students and teachers. The presence of native-speaker teachers from various Arab countries further supports the creation of a natural and communicative language environment. In addition, the school culture that habituates students to continuous Arabic use helps students understand and apply Arabic in daily life. This study concludes that bi'ah lughawiyyah significantly influences the success of students’ Arabic language acquisition and offers a unique contribution by highlighting the integration of fusha and amiyah within a multicultural Arabic learning environment in Indonesia.